Identification of Students’ Comprehension of Radiation Concept Using Rasch Analysis - Bilqis, Ayesha; Nurhanivah, Devi; Ramdhani, Saumi Zikriani; Taufani, Muhammad Rizka; Aminudin, Adam Hadiana; Kuncoro, Alvina Kusumadewi; Syamsiah, Endah Nur; Ulya, Naily; Aningsih, Sri (International Journal of Research in Community Services, 2024)
This community service was conducted using a survey method. The survey aimed to test the understanding of high school students regarding the dangers of radiation exposure from the surrounding environment. Participants in this activity were 48 students (35 science students and 13 social science students) from a high school in Majalaya, Bandung Regency. The instrument used was a two-tier diagnostic test consisting of 4 essay questions related to physics concepts concerning radiation exposure. The analysis of the test results was divided into two parts: conception analysis and Rasch analysis. The conception analysis was done by interpreting students' answers and categorizing them into five conception categories: Full Understanding (FU), Partial Understanding (PU), Misconception (MC), Not Understanding (NU), and No Coding (NC). This categorization was presented in percentage form. The Rasch analysis was conducted based on the distribution of students' answers and item bias detection to identify the spread of students' answers to each question item and the biases present. First, the conception analysis results showed that 53% of students were included in the FU category, while only 5% were in the Not Understanding (NU) category. This indicates that students' understanding of the dangers of radiation exposure is quite good, as more than half of the participants are in the FU category. Second, the Rasch analysis results based on the distribution of students' answers showed that more students could answer basic comprehension questions compared to classification and analysis-based questions. Additionally, the Rasch analysis results based on item bias detection indicated that there was no gender or academic major bias in the four question items.